FORMATION OF THE PROFESSIONAL WORLDVIEW OF YOUNG PEOPLE (Conferencea, 2022)
The theoretical element of the worldview opens the movement from the direct sensory reflection of reality to abstract conceptual thinking. However, conceptual thinking is not the final point of scientific and educational cognition - after that, the ascent from the abstract to the concrete begins, which is not a simple return to the original, but to the concrete at a higher stage of its development, when the subject is comprehended deeply and comprehensively.